Orientation‐Dependent Intercalation Channels for Lithium and Sodium in Black Phosphorus. Issue 46 (7th October 2019) - Kim, Sungkyu; Cui, Jiang; Dravid, Vinayak P.; He, Kai
Abstract: Black phosphorus (BP) with unique 2D structure enables the intercalation of foreign elements or molecules, which makes BP directly relevant to high‐capacity rechargeable batteries and also opens a promising strategy for tunable electronic transport and superconductivity. However, the underlying intercalation mechanism is not fully understood. Here, a comparative investigation on the electrochemically driven intercalation of lithium and sodium using in situ transmission electron microscopy is presented. Despite the same preferable intercalation channels along [100] (zigzag) direction, distinct anisotropic intercalation behaviors are observed, i.e., Li ions activate lateral intercalation along [010] (armchair) direction to form an overall uniform propagation, whereas Na diffusion is limited in the zigzag channels to cause the columnar intercalation. First‐principles calculations indicate that the diffusion of both Li and Na ions along the zigzag direction is energetically favorable, while Li/Na diffusion long the armchair direction encounters an increased energy barrier, but that of Na is significantly larger and insurmountable, which accounts for the orientation‐dependent intercalation channels. The evolution of chemical states during phase transformations (from Li x P/Na x P to Li3 P/Na3 P) is identified by analytical electron diffraction and energy‐loss spectroscopy. The findings elucidate atomistic Li/Na intercalation mechanisms in BP and show potential implications for other similar 2D materials. Abstract : The intercalation of lithium and sodium in black phosphorus with orientation‐dependent channels and distinct anisotropic pathways is discovered using in situ transmission electron microscopy combined with density functional theory calculations. The atomic structure evolution along zigzag and armchair directions and the relevant changes in chemical states are elucidated, which offers a fundamental understanding of intercalation mechanisms.